2013
DOI: 10.7314/apjcp.2013.14.7.4209
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-2 Gene Expression in Human Breast Cancers in Iran

Abstract: Background: Breast cancer is among the five most common cancers and ranks first among cancers diagnosed in Iranian women. Screening and treatment of this disease with molecular methods, especially regarding high incidences at early age and advanced stage, is essential. Several genes with altered expression have been identified by cDNA microarray studies in breast cancer, with the Bcl-2 gene indicated as a likely candidate. In this study, we studied Bcl-2 gene expression levels in parallel tumor and non-tumor b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
5
1
Order By: Relevance
“…Rostamizadeh et al demonstrated the higher expression levels of the Bcl-2 gene in tumor samples compared with marginal samples, however, this was not a significant difference (p>0.05). (Rostamizadeh et al, 2013). But, In our study The level of the expression of BCL2 gene in control group increased compared with non tumoural marginal and tumoural group.…”
Section: Discussioncontrasting
confidence: 46%
“…Rostamizadeh et al demonstrated the higher expression levels of the Bcl-2 gene in tumor samples compared with marginal samples, however, this was not a significant difference (p>0.05). (Rostamizadeh et al, 2013). But, In our study The level of the expression of BCL2 gene in control group increased compared with non tumoural marginal and tumoural group.…”
Section: Discussioncontrasting
confidence: 46%
“…BCL-2 over expression was positively associated with tumor grade and ER/PR, and negatively with tumor size. There was also a significant correlation between high levels of BCL-2 mRNA expression and survival rates [58]. PTEN is a tumor suppressor via the stimulation of apoptosis in tumor cells and suppression of cell proliferation.…”
Section: Main Textmentioning
confidence: 99%
“…Breast cancer is one of the three most common cancer in Iranian population and the highest rate of cancers diagnosed among Iranian women. Although the incidence rate of breast cancer in Iranian women is almost six times lower than Caucasian women in the United States (23.65 per 100,000 to 140.8 per 100,000), but the number of newly diagnosed cases is rising rapidly (8)(9)(10). Breast cancer is very poor prognosis and there are limited therapeutic options for patients with advanced and metastatic forms.…”
Section: Introductionmentioning
confidence: 99%